2017
DOI: 10.1002/jor.23712
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysregulation accelerates injury‐induced joint degeneration, driven by local inflammation; an in vivo rat study

Abstract: Evidence is growing for the existence of an obesity-related phenotype of osteoarthritis in which low-grade inflammation and a disturbed metabolic profile play a role. The contribution of an obesity-induced metabolic dysbalance to the progression of the features of osteoarthritis upon mechanically induced cartilage damage was studied in a rat in vivo model. Forty Wistar rats were randomly allocated 1:1 to a standard diet or a high-fat diet. After 12 weeks, in 14 out of 20 rats in each group, cartilage was mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…We previously showed that the observed progression of joint degeneration in this model was mainly inflammatory driven. 22 We observed a clear increase of activated macrophages in the specific joint tissues compared with sham operated contralateral controls.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We previously showed that the observed progression of joint degeneration in this model was mainly inflammatory driven. 22 We observed a clear increase of activated macrophages in the specific joint tissues compared with sham operated contralateral controls.…”
Section: Discussionmentioning
confidence: 56%
“… 21 On the other hand, when cartilage damage is mechanically induced in addition to high-fat (HF) diet feeding, an inflammatory driven increase in joint degeneration was observed. 22 The role of folate receptor expressing macrophages in both OA models is currently unknown. We hypothesized that accumulation of the novel folate radioconjugate in the target tissue may be visualized in the rat groove model on both a standard diet and a HF diet.…”
Section: Introductionmentioning
confidence: 99%
“…The animal model most thoroughly examined in the context of metabolic OA is the C57BL/6J mouse strain, or genetic variants based on this background, as the readily obtained obesity observed in C57BL/6J mice closely parallels the metabolic adaptations seen in human disease pathogenesis 11 . Most researchers have employed the very high-fat diet (VHFD), a high-fat diet with a supraphysiological fat content of 60 kcal% energy from fat, to induce metabolic OA in male mice e occasionally combined with an increased mechanical burden through surgery or exercise 12,13 . In contrast, published experimental designs vary greatly in study duration and age at start, which are important determinants of the capacity for metabolic adaptation and ultimately of the severity of metabolic OA.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have employed the very high-fat diet (VHFD), a high-fat diet with a supraphysiological fat content of 60 kcal% energy from fat, to induce metabolic OA in male mice e occasionally combined with an increased mechanical burden through surgery or exercise 12,13 . In contrast, published experimental designs vary greatly in study duration and age at start, which are important determinants of the capacity for metabolic adaptation and ultimately of the severity of metabolic OA.…”
mentioning
confidence: 99%
“…Articular cartilage defect is a formidable clinical problem with cartilage degeneration or loss, which is difficult to treat and slow to develop. 1,2 When cartilage defects occur, there is no support for new cartilage growth to climb in or across the defect. Furthermore, the defect interval is too wide for the chondrocytes to migrate.…”
Section: Introductionmentioning
confidence: 99%